PUPILLARY REWARD SENSITIVITY IS A MARKER OF APATHY IN PARKINSON'S DISEASE. Issue 12 (15th November 2016) - Muhammed, Kinan; Yehuda, Michael Ben; Drew, Daniel; Manohar, Sanjay; Chong, Trevor; Tofaris, George; Bogdanovic, Marko; Lennox, Graham; Hu, Michele; Husain, Masud
Abstract : Apathy, a syndrome characterized by lack of motivation, is common across neurodegenerative conditions. Although it is now established to be associated with poor quality of life, mechanisms underlying the condition are poorly understood. Here we used two novel incentivised oculomotor paradigms to measure reward sensitivity in 30 Parkinson's disease (PD) patients, both ON and OFF dopaminergic medication, comparing them to age-matched controls. To distinguish between pupillary response to anticipated reward vs. response associated with motor preparation, a Go/NoGo version was performed in a further 20 PD cases. Reward sensitivity, indexed by pupillary dilation for reward, was greater in controls and PD ON compared to OFF (p<0.01). There was a significant correlation between pupil reward sensitivity and clinical apathy in PD (p<0.001), with apathetic individuals displaying less reward sensitivity. Pupillary reward sensitivity was observed regardless of whether a saccade was required. On diffusion-weighted MR imaging, reward sensitivity correlated with fractional anisotropy in the caudal cingulate zone of controls (p<0.05), an area previously implicated in motivation. Reward insensitivity may underlie lack of motivation in PD and is quantifiable using pupillary responses to rewards, independent of motor preparation. Dopaminergic medication can increase reward sensitivity and may be effective therapy for apathy, independent of motor control.